Plasmodium falciparum Cyclic Amine Resistance Locus (PfCARL), a Resistance Mechanism for Two Distinct Compound Classes - Pamela Magistrado; Victoria Corey; Amanda K. Lukens; Greg LaMonte; Erika Sasaki; Stephan Meister; Melanie Wree; Elizabeth A. Winzeler; Dyann F. Wirth (2016)
MMV007564 is a novel antimalarial benzimidazolyl piperidine chemotype identified in cellular screens. To identify the genetic determinant of MMV007564 resistance, parasites were cultured in the presence of the compound to generate resistant lines. Whole genome sequencing revealed distinct mutations in the gene named Plasmodium falciparum cyclic amine resistance locus (pfcarl), encoding a conserved protein of unknown function. Mutations in pfcarl are strongly associated with resistance to a structurally unrelated class of compounds, the imidazolopiperazines, including KAF156, currently in clinical trials. Our data demonstrate that pfcarl mutations confer resistance to two distinct compound classes, benzimidazolyl piperidines and imidazolopiperazines. However, MMV007564 and the imidazolopiperazines, KAF156 and GNF179, have different timings of action in the asexual blood stage and different potencies against the liver and sexual blood stages. These data suggest that pfcarl is a multidrug-resistance gene rather than a common target for benzimidazolyl piperidines and imidazolopiperazines.